Efficacy and safety of Chinese herbal medicine for pneumonia convalescence in children: A systematic review and meta-analysis - Guo, Jian-Ning; Bai, Xue; Zhang, Hong-Xian; Zhang, Ning; Liang, Jun-Ming; Guo, Zi-Yi; Cui, Xia (Frontiers in Pharmacology, 2022)
Background: Chinese herbal medicine (CHM) has advantages in treating sequela symptoms of pediatric pneumonia convalescence. Hence, this study aims to evaluate the efficacy and safety of CHM using a meta-analysis approach. Methods: The randomized controlled trials (RCTs) that met the search strategy were selected from seven databases from the inception date to December 17, 2021. Based on the Cochrane handbook, the quality of the selected studies was assessed using the risk of bias. Data were expressed as relative risk (RR) or mean difference (MD) and with 95% confidence interval (CI). Subgroup analyses and sensitivity analyses were performed. The Grading Recommendation Assessment, Development, and Evaluation (GRADE) method was used to assess the evidence certainty. Result: Twenty RCTs with 2,241 participants were identified using the search criteria. CHMs included Danshen injection, Liujunzi decoction, Qingfei Tongluo decoction, Yiqi Huoxue decoction, Yupingfeng granule, XiaoErFeiKe granule, Sha-Sheng-Mai-Dong decoction, and so on. Results indicated that CHM combined with Western medicine (WM) or CHM alone improved the total clinical effective rate (RR = 1.22; 95% CI: 1.15–1.29), reduced cough relief time (MD = −2.16; 95% CI: −2.46 to −1.85), lung rales disappearance time (MD = −1.82; 95% CI: −2.17 to −1.47), and length of hospital stay (MD = −2.01, 95% CI: −3.81 to −0.22) in the treatment of pneumonia convalescence in children. However, there was no significant statistical difference regarding the incidence of adverse reactions (RR = 0.57; 95% CI: 0.23–1.43). Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/; Identifier CRD42022298936